Expanding the history of humanities computing: Hugh Kenner's conversational criticism. - Roach, Rebecca (Digital Scholarship in the Humanities, 2023)
This article posits that a novel and humanistic model of computing—'conversational computing'—would emerge in the 1960s which, despite being largely forgotten today, proved extremely influential in computing and wider culture. I examine the metaphor and model of conversation embedded in this earlier idea and trace the ways it was taken up in the humanities via examining, through his archives, the career of renowned literary critic and programmer, Hugh Kenner (1923–2003).